HUBUNGAN ANTARA SELF-EFFICACY DAN KOHESIVITAS DENGAN KOMUNIKASI ANTARPRIBADI - Rosyadah, Hani (Indonesian Journal of Guidance and Counseling: Theory and Application, 2014)
Interpersonal communication is essential for student affairs A Guidance and Counseling as a potential counselor because preparation to help foster effective and efficient communication with the counselee. The purpose of this study was to determine the relationship jointly between self-efficacy and cohesiveness with interpersonal communication. This research is descriptive quantitative. Population and sample are all students Department of Guidance and Counseling, amounting to 361 students with a sampling technique using proportional random sampling, the samples were taken is 30% of the study population. Means of data collection using a scale of interpersonal communication that has tested its validity the product moment formula and the reliability of the instrument with alpha formula. Analysis of data using multiple regression. The results of this study indicate that there is a significant relationship jointly between self-efficacy with interpersonal communication, the value of F count = 15,710 with sig = 0.000 <0.05 . The conclusion of this study that there is a significant relationship together between self-efficacy with interpersonal communication. It is hoped advisable for the Department of Guidance and Counseling to provide innovation activities that can improve interpersonal communication, self-efficacy and cohesiveness.